A tale of two cousins: Ependymal cells, quiescent neural stem cells and potential mechanisms driving their functional divergence. (6th June 2019) - Stratton, Jo Anne; Shah, Prajay; Sinha, Sarthak; Crowther, Emilie; Biernaskie, Jeff
Abstract : Recent work has suggested that stem cells exhibit far greater heterogeneity than initially thought. Indeed, their dynamic nature and shared traits with surrounding niche cells have made prospective identification of adult neural stem cells (NSCs) challenging. Refined fate mapping strategies and single‐cell omics techniques have begun to clarify functionally distinct states within the adult NSC pool, the molecular signatures that govern these states, and the functional contributions/interactions with neighboring cells within the subventricular niche. Ependymal cells are the epithelial cells which line the ventricular system and reside in the same niche as NSCs. Our own work has revealed that, despite sharing similar embryonic origins with NSCs and close geographic proximity, ependymal cells are transcriptionally distinct and fail to exhibit stem cell function in vivo, even following injury. Intriguingly, comparison of ependymal cells with qNSCs revealed transcriptional signatures that are largely overlapping, suggesting that post‐transcriptional regulation might underlie their divergent phenotypes. Additional analysis of ependymal versus qNSC gene regulatory network activation supports this notion. This Viewpoint summarizes the historical confusion regarding the identity of NSCs within the lateral ventricle niche and describes recent work that provides greater appreciation for the diverse functional states within the NSC niche. Abstract : Ependymal cells are accessible for drug targeting via the cerebral spinal fluid (CSF) making them an ideal target for therapeutic manipulation. Ependymal cells share several transcriptional similarities with quiescent neural stem cells (qNSCs) and both arise from radial glial cells (RGCs), yet they are governed by unique gene regulatory networks. Therapeutic manipulation via re‐ or de‐programming could unleash their capacity to contribute to regeneration following brain injury.